Legal issues in joint developments of South Korea and Kazakhstan in the field of subsoil use - Zharmakhanbetova, B.A.; Saktaganova, A.B.; Saktaganova, I.S. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2024)
South Korea and Kazakhstan are actively developing cooperation in the field of subsoil use, seeking to combine their resources and technological capabilities for mutually beneficial partnership. Kazakhstan, which has rich mineral reserves, attracts investments and the experience from South Korea for the effective management and development of its natural resources. At the same time, South Korea, which needs stable supplies of raw materials, gets access to Kazakh resources, which contributes to the diversification of its sources of raw materials and strengthening economic security. The key areas of cooperation are the exploration and production of oil, natural gas, rare earth elements and other minerals. Joint projects include the creation of modern mining enterprises, the introduction of advanced technologies and the exchange of experience in the field of environmentally sound subsoil use. Both States are also working to create favorable conditions for investments and develop a regulatory-legal framework that promotes long-term and sustainable development of the subsurface use sector. Such cooperation allows Kazakhstan to improve infrastructure and attract modern technologies, which contributes to the sustainable development of the national economy. For South Korea, the partnership with Kazakhstan opens up new opportunities to expand its presence in the international resource market and strengthen economic ties with Central Asia.